The Onset of Glucose Dysregulation Among Adults Treated with Antipsychotics: A Systematic Review of Cohort Studies - Riri Erwina Putri; Hedya Nadhrati Surura (Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh, 2026)
Antipsychotic pharmacotherapy, particularly second-generation agents, is widely recognized for its efficacy in psychotic disorders but is strongly associated with adverse metabolic consequences, including disturbances in glucose homeostasis in addition to weight gain and dyslipidemia, though the precise time-to-onset of glucose dysregulation under real-world conditions remains insufficiently characterized. This systematic review aimed to synthesize cohort evidence on the incidence and timing of glucose dysregulation in adults treated with antipsychotics. Following PRISMA guidelines, systematic searches were conducted in PubMed, Scopus, and ScienceDirect for cohort studies published in the past five years, focusing on adult patients with outcomes including fasting plasma glucose, HbA1c, oral glucose tolerance test results, or incidence of diabetes mellitus, with methodological quality appraised using the Cochrane Risk of Bias 2 tool. Eight cohort studies with more than 60,000 participants and follow-up durations ranging from one to twenty years were included, showing that glucose dysregulation often emerged within 6–12 months of initiating high-risk agents such as clozapine and olanzapine, with cumulative risk increasing over prolonged exposure. Baseline factors such as elevated BMI, dyslipidemia, and family history of diabetes were consistently associated with earlier onset, while structured inpatient environments with diet and exercise interventions appeared to mitigate metabolic deterioration despite long-term clozapine use. Overall, antipsychotic treatment in adults is consistently linked to an increased risk of glucose dysregulation, typically arising within the first months to years of therapy, highlighting the importance of proactive monitoring from treatment initiation and the implementation of preventive strategies to reduce long-term cardiometabolic burden. Keywords : Antipsychotics, Glucose dysregulation, Diabetes mellitus, Cohort studies